Emerging Transit Technology: Implementing an Urban Gondola System over Al Corniche, Doha, Qatar - A Cost Estimation Study - Tahmasseby, Shahram (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Urban gondolas are a type of driverless transit vehicles, which are increasingly drawing the attention as a viable mass transit alternative in urban environments and touristic areas. The system is distinctive with high reliability of travel time, because it operates on their own right of. Urban gondolas are also identified with environmental benefits resulting from their low emission, energy use, and noise pollution. They have widely been implemented in touristic areas, mountains and in areas with diverse topography types. The objective of this study is a first step assessment of the potential economic viability of implementing an urban Gondola linking East Mound Skyline View to the promenade side along Al Dafna Park in Westbay Doha, Qatar. The focus of this study is on introducing an appropriate technology plus estimating its associated cost components of implementing such system in Qatar. The (Monocable) urban gondola technology will be investigated in terms of applicability and furthermore, their associated cost components including the capital costs such as infrastructure civil works, as well as operating and maintenance costs (O&M) will be estimated based on the existing benchmarks and similar practices from around the globe. The result of this study could be a basis for an in-depth Cost-Benefit Analysis of implementing emerging transit technologies (e.g. urban gondola) in the State of Qatar.